Silicon-Based-Chip Multiplexing Technologies and Devices - Daoxin Dai; Jian Wang; Sitao Chen (Dianxin kexue)
As the demands of the data communications increase quickly for the applications of cloud-computing as well as data centers，optical interconnects have been very attractive because of the unique advantages on the aspects of low power consumption，high speed and large bandwidth.It is effective to enhance the link capacity by utilizing multiplexing technologies like wavelength-division-multiplexing（WDM），polarization-division-multiplexing（PDM），as well as mode-division-multiplexing（MDM）.It will become very useful when these multiplexing technologies are combined to work together as a hybrid multiplexing technology.Definitely the multiplexer is one of the most important devices for a multiplexed optical interconnect link.A review for the recent progress of ultracompact on-chip multiplexers was given，including WDM devices，PDM devices，MDM devices，and hybrid multiplexers.